2022
DOI: 10.3390/jcm11195744
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Drones in Out-of-Hospital Cardiac Arrest: A Scoping Review

Abstract: Drones may be able to deliver automated external defibrillators (AEDs) directly to bystanders of out-of-hospital cardiac arrest (OHCA) events, improving survival outcomes by facilitating early defibrillation. We aimed to provide an overview of the available literature on the role and impact of drones in AED delivery in OHCA. We conducted this scoping review using the PRISMA-ScR and Arksey and O’Malley framework, and systematically searched five bibliographical databases (Medline, EMBASE, Cochrane CENTRAL, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In this regard, solutions are being sought that involve delivering a de brillator to the home where it is located. This concept could be based on First Responders or use Drones [23][24][25][26][27]. Of course, in both cases it is necessary to use an effective communication response system starting with the medical dispatcher [21,23,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, solutions are being sought that involve delivering a de brillator to the home where it is located. This concept could be based on First Responders or use Drones [23][24][25][26][27]. Of course, in both cases it is necessary to use an effective communication response system starting with the medical dispatcher [21,23,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Simulation studies also in suburban areas at a distance of 5 to10 km from the AED base were performed over time. The results were promising and research teams showed the feasibility of drone usage also in these conditions [6][7][8] . One of the few prospective studies on this theme was led by colleagues from Karolinska Institute.…”
Section: Drones and Aedmentioning
confidence: 90%
“…[19]. Clear instruction, possibly by telephone dispatchers [20] and training and information campaigns via media and social media may be required to familiarise the public with delivered defibrillators [21][22][23]. Some initiatives have examined the possibility of delivery to the location of a mobile telephone to ensure an accurate delivery location and also delivering to community first responders to ensure that an effective user is immediately available to operate the defibrillator [24].…”
Section: Transport and Delivery Of Defibrillators To Victims Of Cardi...mentioning
confidence: 99%